Diversity of anopheline mosquitoes (Diptera: Culicidae) and classification based on the characteristics of the habitats where they were collected in Puerto Iguazú, Misiones, Argentina. Issue 2 (17th November 2016) - Ramirez, P.G.; Stein, M.; Etchepare, E.G.; Almiron, W.R.
ABSTRACT: In order to extend the knowledge of anopheline diversity and their habitats in three environments with different degrees of anthropic intervention in Puerto Iguazú, Misiones, anopheline larvae were collected and classified on the basis of similarities of their habitats. Spatio‐temporal abundance was determined and larval diversity and complementarity index were calculated. Rank‐abundance curves were performed to compare the composition, abundance, and species evenness among environments. A total of 783 larvae, belonging to six species: Anopheles argyritarsis, An. fluminensis, An. mediopunctatus, An. punctimacula, An. strodei s.l., and An. triannulatus s.l., were collected. A cluster analysis and a principal component analysis detected two groups; exposure to sunlight and type of habitat were the characteristics that explained the grouping of species. Higher abundances of anopheline larvae were observed during autumn and spring. The greatest richness was recorded in wild and peri‐urban environments and the effective number of species was greater in the wild. Anopheles punctimacula and An. triannulatus s.l. are secondary vectors of malaria in other South American countries and both species were found in the three environments, so that deforestation poses a potential risk for malaria transmission as it contributes to the proliferation of larval habitats for these mosquitoes.